Can subsistence farmers commercialize? Evidence from the southern highlands of Tanzania - Hosea Mpogole; Boniface Kauki; Baltazar Namwata; Emma Ngilangwa; Christina Mandara; Emmanuel Hauli (Farming System)
Improving rural livelihoods remains a challenge due to subsistence production. This study uses 206 surveys to assess whether smallholders can go commercial. We conducted the surveys in eight villages of the southern highlands of Tanzania, which we prioritized based on market access (low, high) and integration into commercial food systems (low, high). In addition, we included eight focus group discussions and six key informant interviews to supplement the survey data. We analyzed survey data using descriptive statistics and the general linear model with robust standard errors. Significant findings are fivefold. First, men dominate crops perceived as commercial, and women are less likely to be commercial. Second, youth are more likely to be commercial than adults. Third, smallholders are willing to quit farming over employment. Fourth, over half of surveyed smallholders perceived themselves as commercially oriented to a small extent, moderate, or great extent. Fifth, factors such as the sex of smallholders, age, land ownership, access to extension services, household size of the smallholder, and ownership of assets influenced the commercial orientation of smallholders. The study concludes that smallholders can indeed and gradually go commercial, albeit on a small scale and within the existing farming systems.